Vegetable Seed Production, 3rd Edition - George, Raymond A.T (CABI, 2014)
Vegetable crop production is one of man’s basic skills. Wherever humans have settled for long enough to produce a crop, they have cultivated vegetables for food and for animal fodder. The level of success and productivity originally depended on the local climate, seasons and the range of species cultivated. The cultivated species were developed by selection from local wild plants and subsequently supplemented by plant introductions from other areas, and later still from other continents. The story of cultivation has been described and discussed in interesting detail by Thoday (2007). It is now being recognized that, in addition to their role as part of a balanced diet, vegetables can play a vital role in agricultural and social development processes. The Asian Vegetable Research and Development Center (AVRDC, 1998) has produced a plan that includes specific programmes such as the inclusion of vegetables in cereal-based systems and year-round vegetable production systems. The plan recognizes, and takes into account, the social and economic values of vegetables. The pivotal role played by seeds in the development of civilization has been described by MacLeod (2007), who points out that seeds are a means of transferring genetic information from generation to generation, in addition to the essential nutrition and energy for germination, emergence and plant establishment. All of our vegetable species have developed as a result of generations of plantsmen selecting and growing the next generation from plants that have displayed the most desirable or useful characters or traits. A successful vegetable production industry is very dependent upon a sustainable supply of satisfactory seeds. At the present time the seed industry plays an important role in both production and distribution of high-quality vegetable seeds. However, there are some communities where ‘own seed’ or ‘on-farm’ seed production is still the norm.